Interlayer Transition in a vdW Heterostructure toward Ultrahigh Detectivity Shortwave Infrared Photodetectors. (21st October 2019) - Qi, Tailei; Gong, Youpin; Li, Alei; Ma, Xiaoming; Wang, Peipei; Huang, Rui; Liu, Chang; Sakidja, Ridwan; Wu, Judy Z.; Chen, Rui; Zhang, Liyuan
Abstract: Van der Waals (vdW) heterostructures of 2D atomically thin layered materials (2DLMs) provide a unique platform for constructing optoelectronic devices by staking 2D atomic sheets with unprecedented functionality and performance. A particular advantage of these vdW heterostructures is the energy band engineering of 2DLMs to achieve interlayer excitons through type‐II band alignment, enabling spectral range exceeding the cutoff wavelengths of the individual atomic sheets in the 2DLM. Herein, the high performance of GaTe/InSe vdW heterostructures device is reported. Unexpectedly, this GaTe/InSe vdWs p–n junction exhibits extraordinary detectivity in a new shortwave infrared (SWIR) spectrum, which is forbidden by the respective bandgap limits for the constituent GaTe (bandgap of ≈1.70 eV in both the bulk and monolayer) and InSe (bandgap of ≈1.20–1.80 eV depending on thickness reduction from bulk to monolayer). Specifically, the uncooled SWIR detectivity is up to ≈10 14 Jones at 1064 nm and ≈10 12 Jones at 1550 nm, respectively. This result indicates that the 2DLM vdW heterostructures with type‐II band alignment produce an interlayer exciton transition, and this advantage can offer a viable strategy for devising high‐performance optoelectronics in SWIR or even longer wavelengths beyond the individual limitations of the bandgaps and heteroepitaxy of the constituent atomic layers. Abstract : GaTe/InSe van der Waals heterostructure photodetectors present an extraordinary detectivity D * (10 14 –10 12 Jones) in a shortwave infrared spectrum of 1.0−1.55 µm forbidden by the bandgap limits of the constituent GaTe and InSe, which is attributed to the formation of the interlayer transition in the type‐II band alignment heterostructure.